Public perception of police performance in crimes control in Anambra State of Nigeria - Onwuama, O. P. (African journal of law and criminology, 2019)
The prevalence of crime and criminality continues to pose a great challenge to the people and government of Nigeria, especially the police, whose constitutional responsibility it is to tackle the menace. Despite the public outcry and government’s effort via the security agents, the scourge of crime seems increasingly insurmountable. This study explored public perception on the performance and efforts of the police in tackling the menace in Anambra State. In-depth interview data was collected from the public especially the elite, such as top civil servants, lecturers, doctors, etc. who are presumably intelligent, enlightened and well-informed to ensure accuracy and correctness of information. The people expressed some knowledge and concern on the devastating level of crime in the society. Some expressed disappointment and hopelessness with the police and their corrupt attitude in the face of the turbulence. The desire for police-public partnership or cooperation was highlighted to effectively and drastically reduce crime and criminality. The study recommends that the police should exhibit capacity, expertise, efficiency and professionalism in tackling the incidences of crime and criminal elements to win public confidence again.